Generation and Characterization of Induced Pluripotent Stem Cells and Retinal Organoids From a Leber’s Congenital Amaurosis Patient With Novel RPE65 Mutations - Li, Guilan; Gao, Guanjie; Wang, Panfeng; Song, Xiaojing; Xu, Ping; Xie, Bingbing; Zhou, Tiancheng; Pan, Guangjin; Peng, Fuhua; Zhang, Qingjiong; Ge, Jian; Zhong, Xiufeng (Frontiers in Molecular Neuroscience, 2019)
RPE65-associated Leber congenital amaurosis (LCA) is one of highly heterogeneous, early onset, severe retinal dystrophy with at least 130 gene mutation sites identified. Their pathogenicity has not been directly clarified due to lack of diseased cells. Here, we generated human induced pluripotent stem cells (hiPSCs) from one putative LCA patient carrying two novel RPE65 mutations with c.200T>G (p.L67R) and c.430T>C (p.Y144H), named RPE65-hiPSCs, which were confirmed to contain the same mutations. The RPE65-hiPSCs presented typical morphological features with normal karyotype, expressed pluripotency markers, and developed teratoma in NOD-SCID mice. Moreover, the patient hiPSCs were able to differentiate towards retinal lineage fate and self-form retinal organoids with layered neural retina and RPE. All major retinal cell types including photoreceptors were also acquired overtime. Compared to healthy control, RPE cells from patient iPSCs had lower expression of RPE65, but similar phagocytic activity and VEGF secretion level. Our findings disclosed that these novel RPE65 gene mutations (c.200T>G and c.430T>C) had no influence on early stage of human retinal development, but down-regulated RPE65 expression in RPE cells. This study provided the valuable patient specific, disease targeted retinal organoids containing photoreceptor and RPE cells, which would facilitate the study of personalized pathogenic mechanisms of disease, drug screening, and cell replacement therapy.